Gender Differences in Business Registers Used by Live Streamers on Tiktok snd Shopee Live - Silvia Eka Widayanti; Fayza Achsina Salsabila (Lingua Franca, 2026)
This research aims to investigate the differences in the business registers used by men and women streamers on TikTok and Shopee. The approach of this research is qualitative, and the data are collected through random sampling and non-participant observation of live streams on TikTok and Shopee, featuring five men and five women streamers, with durations ranging from 10 to 15 minutes. The analysis began with the identification of registers using Martin Joos's theory, which classifies registers into frozen, formal, consultative, casual, and intimate.  Then, elaborating on the reason why different genders use different registers, utilizing the theory from Holmes about language and gender. This study showed that there are three forms of register: Consultative (70%) by men and Consultative (52%), Casual (16%), and Intimate Style (32%) by women. Those are mainly influenced by the purpose of the communication and by women's tendency to use more affective language than men. In conclusion, the registers used by men and women live streamers on TikTok and Shopee are quite similar.